EXPLICATING THE ELUSIVE ‘PEDAGOGICAL REASONING’ OF EXPERT TEACHERS OF SCIENCE - Panizzon, Debra Lee; Keast, Stephen; Mitchell, Ian; Loughran, John (Educere et Educare, 2018)
Quality teaching that enhances student learning and engagement in science is a focus for all educational systems. Whether fuelled by the results from international studies, such as the Programme for International Student Assessment (PISA), or from what is already evident from the research, highly skilled teachers can greatly improve the educational outcomes of students (MOURSHED, CHIJIOKE & BARBER, 2010). It is this fundamental principle that underpins the recent development and implementation of the Australian Professional Standards for Teachers (APSTs), which identify explicitly the qualities that teachers are expected to demonstrate in each of four career stages: Graduate, Proficient, Highly Accomplished, and Lead (Australian Institute for Teaching and School Leadership [AITSL], 2012). Underpinning teacher quality in at least four of these standards is the elusive tacit or pedagogical knowledge that is held and used by ‘expert’ teachers of science in their teaching. The study discussed in this paper set out to explicate the knowledge or ‘pedagogical reasoning’ brought to a teaching context by expert teachers as they plan to teach science. The three-year longitudinal study incorporated two cohorts of teachers representing elementary and high school teachers of science (N = 40) in one state in Australia. Data were collected from audio recordings of pairs of teachers as they designed units of work, interviews with pairs of teachers, and other ad hoc data collected during workshops conducted with the teachers throughout the study. Analyses of these data revealed non-linear, complex, and rapid interactions between five distinct, but richly connected focal concepts that comprise teachers’ pedagogical reasoning. The five focal concepts were termed: Big Ideas; Student Engagement; Quality Learners and Quality Learning; Contextual Constraints and Opportunities; and, Teacher Personal and Professional Identity. The study illustrates the rich web of professional wisdom and pedagogical reasoning that underpins the classroom practices of expert teachers of science and why this knowledge is crucial to understand if we are to nurture our next generation of teachers of science.